If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 11 = 26 Reorder the terms: 11 + x = 26 Solving 11 + x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + x = 26 + -11 Combine like terms: 11 + -11 = 0 0 + x = 26 + -11 x = 26 + -11 Combine like terms: 26 + -11 = 15 x = 15 Simplifying x = 15
| x-26=-5 | | 2x+19y=17 | | 17=m-7 | | 3w^3-12w^2-9w=0 | | 2x-3=4(x+5)-2 | | (x-3)2=(x+9)(x-9) | | 2n-88=n/6 | | 7c=8+6c | | y+7=11 | | y+7=11 | | (y+1)dx+(4x-y)dy=0 | | 7c+8=6c | | 49x^2-56xy+16y^2=0 | | y=-.025(-0.040)(0.0030) | | 195=15x | | 12n-88=n | | 7(x-2)=70 | | -17-3x=6-x | | 205=15x | | 5y-10=30 | | 2k^2+pk=-7 | | 7n=-35-6 | | 5y+2=0 | | (x+4)=x+10 | | (7x+10)=8 | | (5x+8)=52 | | x=0.048*773,000 | | 2x+4y=4y+2x | | -10+x/5=2 | | s/5=300 | | 190,000=x*1,000,000 | | (r+1)(r+1)=14 |